Diagnosis and management of nonmelanoma skin cancer. Issue 5 (May 2017) - Angus, Janet
Abstract : Nonmelanoma skin cancer (NMSC) is the most common form of skin cancer and the prime risk factor is exposure to sunlight. This article describes the main types of NMSC and their clinical presentations, and discusses the management options available.